If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + 4) = -21 Reorder the terms: -3(4 + x) = -21 (4 * -3 + x * -3) = -21 (-12 + -3x) = -21 Solving -12 + -3x = -21 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -3x = -21 + 12 Combine like terms: -12 + 12 = 0 0 + -3x = -21 + 12 -3x = -21 + 12 Combine like terms: -21 + 12 = -9 -3x = -9 Divide each side by '-3'. x = 3 Simplifying x = 3
| 3x-7+5x=-1(4x-7)+17 | | 3(2m+3)+3m=-9 | | 1/4(4x-4)=1/5(5x-10) | | W^2+3w=180 | | -27=-3d | | x(18)=162 | | 3/2y-5/2=-6y-1/5 | | 5(3y-14)+3y=20 | | F(x)=19x+14 | | 5.3-3.24=3.18-5.4x | | 9x-.3=5.9-.2x | | 4+3c=25 | | 5-9x=85 | | -3m-5(3x+7)=0 | | 3x-(-y)=7 | | 16x^7/-4x^3 | | 16x=36-3x | | x^2-16/x^2-3x-4= | | 2=r/3-1 | | 15×1/3 | | 20+x=36-3x | | 5x+3y=316 | | 9x-3(-5x-2)=8x | | 1/8x=50 | | 12x+28=18x-20 | | (8x-8)1.5=64 | | -1=4(3-x*2) | | x+x*x+x*x*x= | | 2x-3(-3)-2=4 | | (4x-16)0.5=36 | | 2(x+1)=-3(3x-2) | | 6.666+x=12-x |